THE EFFECT OF INVOLVEMENT, PUBLIC SERVICE MOTIVATION, AND RED TAPE ON PERFORMANCE - Ahmad, Hafidz Shohihuddin; Rachmawati, Riani (Jurnal Aplikasi Manajemen, 2023)
The public sector of developing countries initiates reforms that frequently center around enhancing the performance of civil servants in response to the growing demands of the work environment. Thus, organizations in the public sector need their employees to be more engaged in their work to achieve high performance. Therefore, this study aimed to investigate the direct association between high-involvement climate, public service motivation, red tape, and employee performance, as well as their indirect influence mediated by work engagement. The analysis was conducted using covariance-based structural equation modeling with the Lisrel application based on data from a questionnaire survey of civil servants under the National Civil Service Agency (NCSA), Indonesia. This study used purposive sampling with 338 respondents selected from the NCSA, based on a minimum sample size of 331 derived from a population of approximately 2400 employees by the Krejcie & Morgan table. The findings of the analysis validated the positive impact of public service motivation and a high-involvement climate on employee performance while revealing the negative effects of red tape, which hindered performance. Additionally, the study demonstrated that public service motivation exerted the most significant direct effect on improving performance, and this relationship was partially mediated by work engagement. Based on the results of this study, it can be concluded that a high-involvement climate and public service motivation can improve performance, red tape can reduce performance, and work engagement is mediating the relationships. Therefore, in improving their employees’ performance, NCSA managers can focus on improving their public service motivation while stimulating their work engagement, improving their involvement, and reducing the impact of red tape.